Empowering Student Talent Development Through Local Wisdom: A Talent-Based Curriculum Model - Illahi, Rilci Kurnia; Yunita, Rahmi; Wahyuni, Ade Sri (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Education in this country is still dominated by a uniform national curriculum that does not fully provide space for the individual development of students' talents. This results in many students' potential not being optimally explored because the learning approach does not take into account cultural context and diversity of talents. This study aims to conduct an in-depth analysis of the implementation of a talent-based curriculum integrated with local cultural values in shaping strategies for developing students' talents. This study employs a qualitative approach with a case study design. The research subjects consist of teachers, school principals, and students involved in the implementation of the talent-based curriculum. Data were collected through in-depth interviews, participatory observation, and document analysis, using instruments such as interview guides, observation sheets, and document checklists. Data were analyzed using inductive thematic analysis with steps of coding, categorization, theme identification, and conclusion drawing. The results of the study indicate that a talent-based curriculum can be effectively implemented through the integration of local cultural values, particularly the philosophy of “Alam Takambang Jadi Guru.” Teachers act as facilitators and mentors in designing adaptive, collaborative, and contextual learning tailored to students' interests and talents in the fields of art, sports, technical skills, and language. In conclusion, the implementation of a talent-based curriculum integrated with local wisdom can create a holistic and empowering learning environment. This research implies the importance of developing a culture-based education model as an innovative alternative in supporting personalized learning and the development of students' talents.